Sistematik Görsel Araştırmalarda Fotoğrafın Yeri: Mimar Sinan Eserleri Örneği - Özkeçeci, İlhan; Böcekler, Burcu; Yavuz, Ozan; Önal, Halil (The Turkish Online Journal of Design Art and Communication, 2014)
Shortly after invention in 19.century, photography had been used in service art research. As well as photographing of paintings, ceramics, chinas, photographs of the most valuable architectural structures are important.Turkey is the most important countries in the world in terms of having Mimar Sinan Mosques which are most rare examples of Turkish Islamic Architecture. But there is still not any institution that contains photographs of Mimar Sinan’s artefacts, performing systematic photographies or sharing of these datas. However, large majority of the researchers needs these kind of visual datas. Relating to the past as well as current status of the mosque photos always required by researchers. Largest sources for history on this topic ,photos of taken with their own means art historians like Oktay Aslanapa. These photos provide great opportunities to researchers on both mosques and their environments. However, the provision of this photographs is very difficult because of personal archives. They put in their book is limited by one or two photos. In this article will be mentioned Mimar Sinan books published in Turkey and the photos situated in this books. Until the early years of Turkish Republic to present day, many boks have been published on Mimar Sinan contains a single structure or his monographs. Most of the photographs in this boks are anonymous or taken by art historians. However, since 1970s in collaboration with art historians and photographers have photographed to provide a more aesthetic view of Sinan’s structures. Another area where the photographs of the artifacts of Mimar Sinan is Internet. Today’s internet opportunities are faced with very intense photographic reserve. However, how can be used and satisfying are these photographs in terms of art historians and other researchers? In this section of article, photographs of Mimar Sinan artifacts will be explored in today’s Internet environment. In the last section, the scientific project name is An Esthetical Analysis of Decorative Elements in Various Ottoman Architectural Works in İstanbul (China-Engraving-Wood-Stone-Marble Pattern, Kaligrafi Compozition) which is systematic photographic project consist of Mimar Sinan’s artefacts’s decoration like engraving, china, wood will be discussed. Photo shoot in the project was carried out today’s latest digital photo techniques. Shootings began with general schemes to show the location of the mosque. After the genral photographs of general structure, focused on decorations such as wood, china, calligraphy located in mosques.
Keywords: Fotoğraf; Mimar Sinan; Görsel Araştırma; Arşiv; Osmanlı Mimarisi; Photography; Visual Research; Archive; Ottoman Architecture